Resveratrol Attenuates Neurodegeneration and Improves Neurological Outcomes after Intracerebral Hemorrhage in Mice - Bonsack, Frederick; Alleyne, Cargill H.; Sukumari-Ramesh, Sangeetha (Frontiers in Cellular Neuroscience, 2017)
Abstract Intracerebral hemorrhage (ICH) is a devastating type of stroke with a substantial public health impact. Currently, there is no effective treatment for ICH. The purpose of the study was to evaluate whether the post-injury administration of Resveratrol confers neuroprotection in a pre-clinical model of ICH. To this end, ICH was induced in adult male CD1 mice by collagenase injection method. Resveratrol (10 mg/kg) or vehicle was administered at 30 min post-induction of ICH and the neurobehavioral outcome, neurodegeneration, cerebral edema, hematoma resolution and neuroinflammation were assessed. The Resveratrol treatment significantly attenuated acute neurological deficits, neurodegeneration and cerebral edema after ICH in comparison to vehicle treated controls. Further, Resveratrol treated mice exhibited improved hematoma resolution with a concomitant reduction in the expression of proinflammatory cytokine, IL-1β after ICH. Altogether, the data suggest the efficacy of post-injury administration of Resveratrol in improving acute neurological function after ICH.